Comprehensive investigation of defects in highly perfect silicon single crystals - Prokopenko, I.V.; Kislovskii, E.N.; Olikhovskii, S.I.; Tkach, V.M.; Lytvyn, P.M.; Vladimirova, T.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We used X-ray diffraction method of total rocking curves and nondestructive direct observation techniques (atomic force and scanning electron microscopies) to quantitatively determine the defect characteristics (radii and concentrations) for the main types of defects in Czochralski-grown silicon single crystals annealed at 750 °С.